2017
DOI: 10.3847/1538-4357/aa6a1f
|View full text |Cite
|
Sign up to set email alerts
|

Panchromatic Hubble Andromeda Treasury. XVIII. The High-mass Truncation of the Star Cluster Mass Function

Abstract: We measure the mass function for a sample of 840 young star clusters with ages between 10-300 Myr observed by the Panchromatic Hubble Andromeda Treasury (PHAT) survey in M31. The data show clear evidence of a high-mass truncation: only 15 clusters more massive than > 10 4 M are observed, compared to ∼100 expected for a canonical M −2 pure power-law mass function with the same total number of clusters above the catalog completeness limit. Adopting a Schechter function parameterization, we fit a characteristic t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
175
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(207 citation statements)
references
References 94 publications
(155 reference statements)
31
175
0
1
Order By: Relevance
“…shear), the maximum cluster mass is not limited by shear, but by feedback disrupting a collapsing cloud before it has coalesced altogether. This updated model yields excellent agreement with observations of clouds, clumps, and clusters from the local Universe out to high redshift, including the lowest maximum cluster mass observed to date (M c = 8 × 10 3 M ⊙ in M31, Johnson et al 2017). Most importantly for the present work, Reina-Campos & Kruijssen (2017) demonstrated that the high-pressure conditions of globular cluster formation (almost) entirely correspond to the shear-limited regime.…”
Section: The Environmental Dependence Of the Maximum Cluster Masssupporting
confidence: 69%
See 1 more Smart Citation
“…shear), the maximum cluster mass is not limited by shear, but by feedback disrupting a collapsing cloud before it has coalesced altogether. This updated model yields excellent agreement with observations of clouds, clumps, and clusters from the local Universe out to high redshift, including the lowest maximum cluster mass observed to date (M c = 8 × 10 3 M ⊙ in M31, Johnson et al 2017). Most importantly for the present work, Reina-Campos & Kruijssen (2017) demonstrated that the high-pressure conditions of globular cluster formation (almost) entirely correspond to the shear-limited regime.…”
Section: The Environmental Dependence Of the Maximum Cluster Masssupporting
confidence: 69%
“…There is a range of observational evidence showing that the cluster mass function has an exponential truncation at the highmass end, both for young clusters (e.g. Gieles et al 2006a;Larsen 2009;Portegies Zwart et al 2010;Johnson et al 2017) and globular clusters (e.g. Fall & Zhang 2001;Jordán et al 2007;Kruijssen & Portegies Zwart 2009).…”
Section: The Environmental Dependence Of the Maximum Cluster Massmentioning
confidence: 99%
“…This is about an order of magnitude lower than the Σ SFR values typical of normal disc galaxies in the Local Universe (Kennicutt 1998). From the relation in Johnson et al (2017), this Σ SFR would correspond to a truncation mass of M c 4000 M , which would naturally explain why Fornax did not form any massive clusters for most of its lifetime.…”
Section: Metallicitiesmentioning
confidence: 85%
“…Using the relation in Johnson et al (2017), this gives a truncation mass of M c = 1.3 × 10 5 M , suggesting that some relatively massive clusters might have formed in NGC 147 during this epoch. Given that there are few, if any, GCs associated with the metal-rich field stars in NGC 147, cluster disruption may indeed have played a more important role in NGC 147.…”
Section: Metallicitiesmentioning
confidence: 99%
“…Johnson et al (2017), studying the YSC population of M31, find that the CMF in this galaxy has a Schechter-type form,…”
Section: Cluster and Compact Association Evolutionmentioning
confidence: 97%